Razlike v zaznavanju gibanja in položaja v gležnju med mlajšimi in starejšimi osebami - Smajla, Darjan (Šport (Ljubljana), 2019)
The aim of the study was to identify reliability of ankle motion sense and active repositioning using a custom-built device, and to determine whether there were (significant) differences for each respective kinaesthetic test between young and older adults. In total, 17 younger and 15 older adults volunteered to participate in this study. Each participant undertook tests on two occasions to identify motion sense ability and active ankle repositioning in the sagittal plane. The reliability analysis revealed good and excellent reliability for motion sense test and active repositioning test for both groups. A higher threshold of ankle motion sense was determined in older adults, while higher absolute errors were identified in two of four reference positions in the older group. In summary, we confirmed acceptable reliability for motion sense and active repositioning test on a custom-built device which can be useful for measuring kinaesthetic sense of the ankle. Our findings showed that aging has an influence on the proprioceptive system which is also reflected by reduced kinaesthetic ability of the ankle between older and younger adults.
Keywords: active repositioning; aging; aktivna repozicija; ankle; gleženj; motion sense; staranje; zaznavanje gibanja